Green Customer Behavior: Mediation Model of Green Purchase - Purnama Alamsyah, Doni; Mulyani,; Udjaja, Yogi; Akhmaliah Othman, Norfaridatul; Rahila Wan Ibrahim, Nik (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to review the correlation of eco-labels on customer behavior, which is green awareness, green trust, and green purchase intention. The study is conducted in Bandung City with a research experimental method on 100 customers of supermarket retail who know about a green product. The study is performed by using SmartPLS and path analysis techniques to find the research model. The research result is known that eco-label has a direct correlation to green awareness and green trust, but it does not relate significantly to green purchase intention. It is the same with green awareness that is insignificant and can change green purchase intention. It is different from a green trust that can switch directly to green purchase intention. The research finding is stated that a customer's green awareness and green trust can genuinely be the correlation mediation of eco-label with green purchase intention. Information from research results provides a positive impact for the company considering green customer behavior and government in giving policy to green product development.